2020
DOI: 10.1111/jcmm.14909
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of hypoxia‐dependent cardiovascular diseases by myo‐inositol trispyrophosphate (ITPP)‐enhancement of oxygen delivery by red blood cells

Abstract: Heart failure is a consequence of progression hypoxia‐dependent tissue damages. Therapeutic approaches to restore and/or protect the healthy cardiac tissue have largely failed and remain a major challenge of regenerative medicine. The myo‐inositol trispyrophosphate (ITPP) is a modifier of haemoglobin which enters the red blood cells and modifies the haemoglobin properties, allowing for easier and better delivery of oxygen by the blood. Here, we show that this treatment approach in an in vivo model of myocardia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Additionally, PTEN activation which leads to the inhibition of PI3K (phosphoinositide 3-kinases) and decreasing tumor AKT (protein kinase B)phosphorylation results in tumor growth reduction [ 156 ]. Moreover, ITPP was described as an effective tool in the treatment of hypoxia-dependent cardiovascular diseases (heart failure) by similar molecular mechanisms [ 185 , 186 ].…”
Section: Endothelial Cells In Angiogenesis and The Role Of Ecs In mentioning
confidence: 99%
“…Additionally, PTEN activation which leads to the inhibition of PI3K (phosphoinositide 3-kinases) and decreasing tumor AKT (protein kinase B)phosphorylation results in tumor growth reduction [ 156 ]. Moreover, ITPP was described as an effective tool in the treatment of hypoxia-dependent cardiovascular diseases (heart failure) by similar molecular mechanisms [ 185 , 186 ].…”
Section: Endothelial Cells In Angiogenesis and The Role Of Ecs In mentioning
confidence: 99%
“…This is accompanied by a potent anti-cancer effect in various tumor models in the mouse 14 , 16 . Moreover, we have recently shown that chronic ITPP treatment partially prevents post-myocardial infarction heart failure in the rat model 17 . However effects of ITPP on myocardial pO 2 have never been studied.…”
Section: Introductionmentioning
confidence: 95%
“…As demonstrated by us, such activation is possible by myo‐inositol trispyrophosphate derivatives in the cancer, 19 but also in cardiac disease 28,44 treatments. It also led us to hypothesize that PTEN activation is a complex process on which its further induced biological consequences are dependent.…”
Section: Discussionmentioning
confidence: 84%